INTERLINGUAL CONTACTS IN THE TERRITORY OF UZBEKISTAN DURING THE PRE-ISLAMIC PERIOD - Zokirov Muxtorali Turdaliyevich (Modern American Journals, 2025)
This article examines the interlingual interactions that took place in the territory of present-day Uzbekistan during the pre-Islamic period, with particular attention to their role in shaping the lexical, phonological, and cultural foundations of the Uzbek language. Situated at the crossroads of the Great Silk Road, the region became a vibrant hub of exchange among diverse civilizations, including Iranian, Greek, Indian, and Chinese cultures. Drawing on archaeological evidence, epigraphic inscriptions, and historical sources, the study demonstrates how the Sogdian, Khorezmian, and Bactrian languages, alongside Greek, Sanskrit, and Chinese, contributed significantly to the enrichment of Uzbek vocabulary and to the development of early written traditions. The findings highlight the extent to which religious-philosophical terminology, administrative and legal vocabulary, as well as trade-related lexicon, entered Uzbek through multilingual contact. By employing a historical-comparative and linguo-cultural approach, the research underscores that the Uzbek language embodies a multilayered heritage shaped by centuries of intercultural communication across Eurasia.
Keywords: Uzbek language; Sogdian; Khorezmian; Bactrian; Greek; Sanskrit; Chinese; Great Silk Road; lexical borrowing; cultural-linguistic contact.